A Model for Physical Education Based Prevent Bullying Instruction for Primary School Students - Yudha Munajat Saputra; Ari Gana Yulianto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Background: Bullying is a persistent issue in primary education, impacting children’s physical, emotional, and social development. Despite efforts to create positive school environments, bullying continues in various forms, including physical, psychological, and cyberbullying. Many prevention programs are reactive rather than proactive, focusing on punishment instead of fostering positive behavior from an early age. Objective: This study aims to develop and evaluate a physical education (PE) based bullying prevention model for primary school students. The model integrates physical activity with social-emotional learning (SEL) to promote a safer, inclusive school environment. Methods: A Systematic Literature Review (SLR) was conducted to examine research on PE based bullying prevention interventions. Studies were selected based on their focus on primary school students, PE, and bullying behaviors. The review followed the PRISMA framework for methodological rigor. Results: The SLR highlights the effectiveness of PE in reducing bullying by promoting positive social behaviors. Key factors include the role of PE teachers, cooperative learning strategies, and SEL integration. Well-structured PE interventions were found to reduce bullying and enhance social skills like empathy and conflict resolution. However, few studies provided a comprehensive PE-based bullying prevention model. Conclusion: This study proposes a PE-based bullying prevention model that integrates physical activity with SEL, fostering a safe and inclusive learning environment. Further research is needed to assess its long-term impact and applicability.